EFEKTIVITAS BP4 KUA KECAMATAN LILIRILAU KABUPATEN SOPPENG DALAM MEMINIMALISIR PERCERAIAN PADA MASA PANDEMI COVID-19 PERSPEKTF HUKUM ISLAM - Rizma Syamwali Putri; Muh. Jamal Jamil; Muh. Rasywan Syarif (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2022)
The main problem in this research is how to review Islamic law on the urgency of the pre-marital course on household harmony at KUA, Mandai District, Maros Regency. From the main problem, two sub-problems were formulated, namely: 1. What is the Urgency of the Pre-Marriage Course on Household Harmony in KUA, Mandai District, Maros Regency?. 2. What is the Urgency of the Pre-Marriage Course on Household Harmony at the KUA, Mandai Sub-district, Maros Regency in terms of Islamic Law? Descriptive Qualitative Research is the type of research used in this thesis, namely field research. The results of this study indicate that the Pre-Marriage Course is very important for every bride and groom to follow as an effort to create a harmonious family by providing knowledge, understanding, skills and raising awareness to adolescents of marriageable age. Second, pre-marital courses have urgency because they contain positive values ​​(maṣlahaḥ) and pre-marital courses strengthen and support the realization of hifẓ an-nasl. The Pre-Marriage Course is carried out so that the prospective bride and groom can get provisions to build a household and can realize household harmony and avoid divorce. The implication of this research is that it is hoped that every prospective bride and groom will take the Pre-Marriage Course seriously so that the bride and groom can get provisions before starting a family. It is hoped that KUA will continue to provide course materials that support harmony in the household of every bride and groom, as well as provide advice on divorce which may occur if husband and wife cannot control the conflict in their household. Keywords: Pre-Marriage Course, Household Harmony.